High diffusivity dense films of a nanoporous-crystalline polymer. (16th August 2021) - Daniel, Christophe; Rizzo, Paola; Nagendra, Baku; Cozzolino, Antonietta; Guerra, Gaetano
Abstract: Nanoporous-crystalline (NC) films of poly(2, 6-dimethyl-1, 4-phenylene)oxide (PPO) exhibit much higher guest uptakes with respect to amorphous PPO films as well as with respect to films based on different polymers. Particularly high guest diffusivities are observed for PPO films with orientation of the chain axes of their NC phases being preferentially perpendicular to the film plane (c⊥ orientation). Remarkably high diffusivities of c⊥ oriented NC PPO films are also observed for high film thickness (at least up to 50 μm). This phenomenon is due to the high free-volume of the amorphous PPO phase combined with crystalline channels being preferentially perpendicular to the film plane. Guest uptakes for NC PPO films, when expressed as mass/volume, are also much higher than for NC PPO powders and high-surface-area NC PPO aerogels, as well as much higher than for benchmark adsorbent polymers (Tenax). High guest uptakes and diffusivities of NC PPO films with c⊥ orientation are relevant for their possible applications as dense membranes for organic pollutant control, molecular separations and molecular sensors. Graphical abstract: Image 1 Highlights: Dense membranes based on PPO for organic pollutant control, molecular separations and molecular sensors. High guest diffusivity in nanoporous-crystalline PPO films with perpendicular orientation of crystalline chain axes. NC PPO films exhibit much higher guest uptakes with respect to NC films of syndiotactic polystyrene (sPS). NC PPO films exhibit much higher guest uptakes than for benchmark Tenax commercial absorbent powders. Guest uptakes for NC PPO films, when expressed as mass/volume, are also much higher than for NC PPO and sPS aerogels.